Bipolar disorder with comorbid attention‐deficit and hyperactivity disorder. Main clinical features and clues for an accurate diagnosis. (20th April 2015) - Torres, I.; Gómez, N.; Colom, F.; Jiménez, E.; Bosch, R.; Bonnín, C. M.; Martínez‐Aran, A.; Casas, M.; Vieta, E.; Ramos‐Quiroga, J. A.; Goikolea, J. M.
<x xml:space="preserve">Abstract</x> Objective To study the prevalence of attention‐deficit and hyperactivity disorder (ADHD) in adult patients with bipolar disorder (BD) and identify differential clinical features for a better diagnosis. Method A total of 163 euthymic bipolar out‐patients were screened for ADHD with the ASRS.V1 and the WURS at a BD Unit. Patients with a positive screening were assessed with the CAADID, at an ADHD unit. Sociodemographic and clinical features of the groups with and without ADHD were compared. Results Lifetime prevalence of comorbid ADHD was 17.9% (10.5% for adult ADHD and 7.4% for childhood ADHD). The BD + ADHD group showed more suicidal behaviour although less severe. Comorbidity was also more common, especially regarding substance use disorders. Nevertheless, these patients did not show more affective episodes or hospitalizations and suffered more atypical but less melancholic depression. However, they required more treatment with psychotherapy and valproate. One‐third of positive screenings at the ASRS were false; a severe course of BD was the hallmark of this subgroup. Conclusion Adult patients with BD and ADHD show differential clinical features, but not a more severe course of BD. Comorbidity with substance abuse is a big issue, deserving special clinical attention. Better screening tools are necessary to avoid overdiagnosis of comorbid ADHD in BD.